Pengaruh Implementasi Strategi Promosi Produk, Harga Dan Kualitas Produk Terhadap Proses Keputusan Pembelian Pada Produk Kosmetik Wardah Saat Pandemi COVID-19 (Studi Pada Mahasiswi FEB Universitas Islam Malang) - Pradiska Tri Kumalasari; Abdul Kodir Djaelani; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine how the effect of the implementation of product promotion strategies, price and product quality on the purchasing decision process of Wardah cosmetic products during the Covid pandemic (Study on FEB Students, Islamic University of Malang). The dependent variable in this study is the purchase decision. And independent variables used, namely product promotion strategy, price and product quality. The population in this study were students of FEB Malang Islamic University. The sample in this study based on Maholtra was taken using purposive sampling technique and measured by multiplying the number (23 indicators x 5) in order to obtain a total sample of 115 respondents according to the theory of Hair dkk. The data collection method used is the method of distributing questionnaires to respondents. The data analysis technique used in this study is multiple linear regression. The results showed that simultaneously the product promotion strategy variables, price, and product quality had a significant effect on purchasing decisions. Meanwhile partially the product promotion strategy variables, price, and product quality have a significant effect on purchasing decisions Keywords: promotion strategy, price, product quality, purchasing decisions